2022
DOI: 10.1002/jlb.4ma0422-288r
|View full text |Cite
|
Sign up to set email alerts
|

Klf10 favorsMycobacterium tuberculosissurvival by impairing IFN-γ production and preventing macrophages reprograming to macropinocytosis

Abstract: By inducing Klf10 expression, Mycobacterium tuberculosis decreases IFN-γ production and impairs an IFN-γ-mediated autocrine loop that promotes macrophage macropinocytosis, thus favoring survival and infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 58 publications
(119 reference statements)
0
4
0
Order By: Relevance
“…Due to the multiple evidence pointing that an excessive inflammation is highly detrimental to the organism 42 , 61 , a therapy focused on promoting phagocytosis could be safer than rising macrophage recruitment. Recent studies have demonstrated that silencing the transcriptional factor Klf10 in macrophages promotes bacterial clarification by augmenting IFN- levels which boosts phagocytosis and bacilli destruction 62 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the multiple evidence pointing that an excessive inflammation is highly detrimental to the organism 42 , 61 , a therapy focused on promoting phagocytosis could be safer than rising macrophage recruitment. Recent studies have demonstrated that silencing the transcriptional factor Klf10 in macrophages promotes bacterial clarification by augmenting IFN- levels which boosts phagocytosis and bacilli destruction 62 .…”
Section: Discussionmentioning
confidence: 99%
“…In the diagram, a synergistic effect was found when both parameters increased simultaneously, requiring almost half the recruitment needed to drive the system to bacterial clearance when is raised by two units, reducing the risk of excessive inflammation. An immunotherapy that increases IFN- 62 and blocks IL-4 and IL-10 cytokines 66 will increase and prevent from decreasing, resulting in an efficient nontoxic therapy. Phagocytosis and recruitment synergy also showed to work even in scenarios where rises.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that silencing the transcriptional factor Klf10 in macrophages promotes bacterial clarification by augmenting IFN-γ levels which boosts phagocytosis and bacilli destruction [43].…”
Section: Discussionmentioning
confidence: 99%
“…In the 𝐹 δ × 𝐹 α 1 diagram, a synergistic effect was found when both parameters rise simultaneously, taking almost half the recruitment needed to lead the system to bacterial clearance when 𝐹 𝛿 is raised by two units, lowering the risk of an excessive inflammation. An immunotherapy that rises IFN-γ [43] and block IL-4 and IL-10 cytokines [47] will rise 𝐹 𝛿 and keep 𝐹 α 1 from dropping which will result in an efficient nontoxic therapy. Phagocytosis and recruitment synergy also showed to work even in scenarios where 𝑃𝑇𝑓 rises.…”
Section: Discussionmentioning
confidence: 99%